2017
DOI: 10.1111/jgh.13676
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram based on preoperative inflammatory markers predicting the overall survival of pancreatic ductal adenocarcinoma

Abstract: Based on clinicopathology characteristics and inflammatory markers, we developed a nomogram providing an individualized risk estimate for PDAC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 35 publications
(67 reference statements)
0
39
0
Order By: Relevance
“…The nomogram developed by Brennan et al [ 5 ] included a large number of variables, such as tumor margins on resection, patient weight loss, and portal vein resection in the study, but the C-index of the model was 0.64, which may be explained by the fact that the study included distal PDAC which has a worse prognosis that PDAC of the head of the pancreas [ 18 ]. The nomogram established by Xu et al [ 11 ] showed high predictive accuracy for the prognosis of PDAC, but the development of the model was based on data from a single center with a small study population, and the standard values of the variables were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram developed by Brennan et al [ 5 ] included a large number of variables, such as tumor margins on resection, patient weight loss, and portal vein resection in the study, but the C-index of the model was 0.64, which may be explained by the fact that the study included distal PDAC which has a worse prognosis that PDAC of the head of the pancreas [ 18 ]. The nomogram established by Xu et al [ 11 ] showed high predictive accuracy for the prognosis of PDAC, but the development of the model was based on data from a single center with a small study population, and the standard values of the variables were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The TNM classification developed by the American Joint Committee on Cancer has been used to estimate the prognosis of cancer. However, there are different prognoses in pancreatic cancer patients whose TNM stages are similar (Xu et al, 2017). Previous clinical research has shown the predictive effect of clinical pathological biomarkers such as tumor heterogeneity, main vessel invasion, and complexity at the genomic, epigenetic, and metabolic levels in patients with pancreatic cancer (Kleeff et al, 2016;Neoptolemos et al, 2018;Naito et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this defect, numerous recent studies have tried to investigate the prognostic significance of the albumin/globulin ratio (AGR) in cancer patients, which combines two factors and thus might reduce the influence of confounding factors. For instance, a body of studies reported that a low pretreatment AGR is closely associated with worse prognosis in patients with digestive system cancers, such as gastric cancer[ 9 , 10 ], colorectal cancer [ 11 – 15 ], pancreatic cancer[ 16 ], hepatocellular carcinoma[ 17 ] and so on. However, most studies published to date use a small sample size, which might affect the reliability of their conclusions.…”
Section: Introductionmentioning
confidence: 99%